Study of thermal behaviour of kaolin clay using dilatometer / Ahmad Zakib Md Yunos and Azmi Harun - Md Yunos, Ahmad Zakib; Harun, Azmi (1994)
Malaysia has relatively large deposits of Kaolin clays and these can be used in manufacture of porcelain, fire brick, china ware, paper and insulation materials. Engineering Ceramics such as alumina , zirconia , silicon nitride and silicon carbide are characterized by good resistance wear , oxidation and corrosion , when compare with metals and thermoplastics [ 4 ]. They have been developed for various applications in metallurgy, in heat engine systems and the aerospace industries. The development of high-performance materials for many branches of modern technology favors technical ceramics rather than metals. With the expectation of specially developed alloys , the so called high-tech ceramic materials are together with polymeric materials , of great importance in terms of the increase in production efficiency , product improvement and energy and raw material saving , as well as decreasing the load on the environment. Worldwide , significant efforts are being made to characterize analytically ceramic materials , optimize the production method and develop the desired product properties applications.